A Comparative Evaluation of Comma-shaped Incision with Standard Incision in Mandibular Third Molar Surgery: A Clinical Study - Pasha, Zameer; Naqvi, Zuber Ahmed; Shaikh, Saleem; Khan, Nazia (Journal of Orofacial Research, 2015)
Objectives: Many series of side effects will be produced with the extraction of impacted lower third molar which including pain, swelling, inflammation, and trismus. Flap design is important to allow good visibility, reach to the impacted tooth, and for healing of the surgically created defect. This study aims at the evaluation and comparison of standard flap design with comma type of flap design used in the surgical extraction of impacted mandibular third molar and to objectively evaluate the merits and demerits of individual flap design. Study design: In this study, 200 patients with bilateral mandibular third molars impaction of age group of 18 to 30 years were selected for the study, To reflect the mucoperiosteal flap on one side standard incision and on other side comma incision were used and, after which the steps are common in the removal of impacted third molars. Immediately on the postoperative days 1, 3 and 7, the postoperative parameters (pain, swelling and mouth opening were recorded. And periodontal status were recorded preoperatively, 1st month and 2nd month respectively. Results and conclusion: The pain and swelling scores were found to be significantly lower in the surgical area with comma incisions which was recorded on days 1, 3 and 7 as compared to the area where standard incisions were made. In mouth opening, there was a sufficiently great difference seen between the two incisions on first postoperative day, but though there was clinical difference between the two incisions on day 3 and 7 there was no statistical significance. The results of the study shows no lingual nerve paresthesia or any other morbidity hence, the new incision design should probably be made the conventional method, considering the less degree of postoperative complications encountered. although it may require some practice initially. Clinical implications: Third molar impactions are common and usually associated with postoperative complications, like pain, swelling, trismus and pocket formation. Incision and flap design is important in healing wound and minimizing postoperative complications. Comma incision design has shown less postoperative complication in compare to standard incision